As relações diplomáticas entre Santa Sé e governo revolucionário de Cuba (1959-2012) - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The sucess of the Cuban Revolution inaugurated a new period in the diplomatic relations with the Holy See. The diplomatic relations were maintained, but there was a great effort by the Vatican to keep alive the Cuban Catholic Church that refused to accept the new Cuban reality. With the end of the Cold War, Holy See and Cuba strengthen the diplomatic relations that is marked Fidel Castro’s visit to Vatican in 1996 and by John Paul’s visit to Cuba in 1998. The Holy See has became a great partner of Cuba in the fight against the economic embargo of the United Sates. From the 2000’s the pontifical diplomacy works harder actively in the release of political prisoners. With Benedict XVI and Raúl Castro the strengthening of relations between the Holy See and Cuba continued developing. Fact that led to the second visit of a Pope to Cuba in 2012.
Keywords: Holy See; Cuba; Diplomatic relations; Cuban revolution; International relations; Revolução cubana; CNPQ::CIENCIAS HUMANAS; Relações internacionais; Relações diplomáticas; Santa Sé; Cuba